"They give you back that dignity": understanding the intangible resources that make a transitional house a home for homeless families. Issue 1 (2nd January 2019) - Fleary, Sasha A.; Joseph, Patrece; Zhang, Emily; Quirion, Catherine
ABSTRACT: Approximately 33% of the homeless population in 2017 were families with children. Researchers have argued for interventions and services to employ an ecological perspective to mitigate some of the unintentional harm inherent in existing programs designed to serve homeless families. This paper utilized a case study of a transitional housing program to (1) determine how well the program met recommendations informed by the ecological perspective and (2) explore underlying themes across recommendations. Past and current residents of a transitional housing program participated in semi-structured interviews as part of a program evaluation. Interviews were deductively and inductively coded to meet aims 1 and 2, respectively. Residents identified several aspects of the program that met the ecological perspective recommendations including culturally-responsive services, trauma-based services, and social and community connections. Major underlying themes spanning across recommendations included interpersonal resources (caring, sense of belonging), empowerment resources (advocacy, family preservation), impact on family (family life, positive youth development), and communication. This case study, through the analysis of residents' perspectives, highlights the important role of transitional housing programs in providing a supportive, empathetic, empowering, and home-like environment that gives residents "back that dignity" so they are emotionally and physically prepared to successfully transition to permanent housing.